If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b = 2b + -1 Reorder the terms: 4b = -1 + 2b Solving 4b = -1 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 4b + -2b = -1 + 2b + -2b Combine like terms: 4b + -2b = 2b 2b = -1 + 2b + -2b Combine like terms: 2b + -2b = 0 2b = -1 + 0 2b = -1 Divide each side by '2'. b = -0.5 Simplifying b = -0.5
| 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 | | 24=1.5+3 | | 168*0.8=134 | | 110=6b+4b | | (x-5)-3=-28 | | 3(9y-2.6)+7.2=6(8y-0.1) | | -5b^2=-180 | | 3y-2x=.5 | | m=-1/4,b=3/5 | | 3c+2c=-95 | | -1.56-2.6y=2.6(y+8.8) | | 18=3s-10+4s | | 9y-8=7y+8 | | 7(x+2.1)=14x-2.8 | | -5x+16=-8(x+1)+6x | | 11=3c+5 | | -1/8z=-6.5 |